Making transparency transparent: a systematic literature review to define and frame supply chain transparency in the context of sustainability - Naemi Schäfer (Management Review Quarterly, 2022)
Supply chain transparency and its connection to sustainability is a current topic in supply chain management research. The term supply chain transparency is used very loosely in this discourse. Therefore, this article aims to clarify the understanding of supply chain transparency in the context of sustainability to enable future research. In a content analysis-based literature review, 92 peer-reviewed articles were identified in the intersection of sustainability, supply chains, and transparency. Only 30 articles contained a definition of transparency. Supply chain transparency was used and defined very differently among the researchers. By providing a general definition and framework of sustainable supply chain transparency, the term "supply chain transparency" gains more clarity. Three dimensions of transparency were identified: sustainable supply chain information, involved stakeholders, and perspective. The supply chain transparency research was conducted primarily in the context of the food and apparel industry. Transparency was characterized differently among the industries and was studied with different foci. Furthermore, the review revealed a focus of supply chain transparency research on the social dimension of sustainability. Additionally, a wide range of topics on supply chain transparency has been covered in the existing literature, and opportunities for future research are outlined. Future researchers are also encouraged to define transparency more clearly.
Keywords: M10; 650; Supply chain transparency; Sustainability; Definition; Framework; Literature review